2004
DOI: 10.1063/1.1842367
|View full text |Cite
|
Sign up to set email alerts
|

Focused-ion-beam-induced deposition of superconducting nanowires

Abstract: Superconducting nanowires, with a critical temperature of 5.2 K, have been synthesized using an ion-beam-induced deposition, with a Gallium focused ion beam and Tungsten Carboxyl, W(CO) 6 , as precursor. The films are amorphous, with atomic concentrations of about 40, 40, and 20 % for W, C, and Ga, respectively. Zero Kelvin values of the upper critical field and coherence length of 9.5 T and 5.9 nm, respectively, are deduced from the resistivity data at different applied magnetic fields. The critical current d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
165
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(195 citation statements)
references
References 42 publications
28
165
1
Order By: Relevance
“…At this point it is worth mentioning that the conductivity can be further increased by employing focused ion beam induced deposition (FIBID) in combination with the precursor W(CO) 6 . Metallic tungsten-based FIBID structures which are also known to become superconducting below 5.2 K, [34][35][36][37] exhibit conductivity values up to 400-680 kS/m exceeding the values for tungsten-based FEBID structures reported here by a factor of 30-50 [34,36,38]. The difference of conductivity between samples prepared by means of FEBID and FIBID is, however, not inherent to deposits fabricated by the dissociation of W(CO) 6 .…”
Section: Resultsmentioning
confidence: 70%
“…At this point it is worth mentioning that the conductivity can be further increased by employing focused ion beam induced deposition (FIBID) in combination with the precursor W(CO) 6 . Metallic tungsten-based FIBID structures which are also known to become superconducting below 5.2 K, [34][35][36][37] exhibit conductivity values up to 400-680 kS/m exceeding the values for tungsten-based FEBID structures reported here by a factor of 30-50 [34,36,38]. The difference of conductivity between samples prepared by means of FEBID and FIBID is, however, not inherent to deposits fabricated by the dissociation of W(CO) 6 .…”
Section: Resultsmentioning
confidence: 70%
“…Disordered or granular W films alloys show significant T c enhancements [3]. The superconductivity of FIB-deposited tungsten was first demonstrated by Sadki et al [4] then by Luxmoore et al [5]. Both groups reported a Tc of 5.2 K for such material and qualitatively ascribe the comparatively high Tc to the absence of long-range order in the material crystal structure.…”
Section: Introductionmentioning
confidence: 92%
“…It has been shown that the resulting deposit is superconducting with T c around 5 K (ref. 27). The precursor gas was injected into the process chamber by means of a needle inserted in the vicinity of the specimen, around 50 mm away in x-y direction and around 150 mm away in the z direction of the substrate surface.…”
Section: Methodsmentioning
confidence: 99%